2021
DOI: 10.1038/s41419-021-03425-0
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-helicase HELLS drives ALK− ALCL proliferation by the transcriptional control of a cytokinesis-related program

Abstract: Deregulation of chromatin modifiers, including DNA helicases, is emerging as one of the mechanisms underlying the transformation of anaplastic lymphoma kinase negative (ALK−) anaplastic large cell lymphoma (ALCL). We recently identified the DNA-helicase HELLS as central for proficient ALK−ALCL proliferation and progression. Here we assessed in detail its function by performing RNA-sequencing profiling coupled with bioinformatic prediction to identify HELLS targets and transcriptional cooperators. We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…2e ). The gene Hells (also known as Lsh ) encodes a SNF2 family DNA helicase that is required for proliferation of mature T lymphocytes and other cell types 19 , 20 , while Tfdp1 encodes for the transcription factor DP-1 that is involved in G1-S cell cycle progression by forming heterodimers with E2F2 stimulating transcription of numerous E2F-dependent genes 21 . Consistent with upregulation of Hells transcription and activity, several Hells- associated cell cycle genes were upregulated at 16 hr by mIL-2/CD25 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e ). The gene Hells (also known as Lsh ) encodes a SNF2 family DNA helicase that is required for proliferation of mature T lymphocytes and other cell types 19 , 20 , while Tfdp1 encodes for the transcription factor DP-1 that is involved in G1-S cell cycle progression by forming heterodimers with E2F2 stimulating transcription of numerous E2F-dependent genes 21 . Consistent with upregulation of Hells transcription and activity, several Hells- associated cell cycle genes were upregulated at 16 hr by mIL-2/CD25 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a member of the GPRIN family, GPRIN1 acts on the classical G protein-coupled receptor pathway [ 46 ]. GPRIN1 is closely related to cancer, and it can promote the proliferation and metastasis of lung cancer by promoting the epithelial-mesenchymal transition of lung cancer cells [ 47 ]. But interestingly, Zhou et al found that GPRIN1 is downregulated in gastric cancer cells and tissues, and it can inhibit the invasion and metastasis of gastric cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the loss of BlackMamba or HELLS leads to a significant inhibition of cell proliferation in ALK -ALCL which is associated with slow rate of duplication and by the increase of multinucleated cells (109). Indeed, these cells showed partial defects in central spindle organization and dramatic defects in cleavage furrow formation impacting on cytokinesis completion (110). This phenotype, strictly attributable to HELLS-dependent regulation of Rho-GTPases, underlines the not always recognized fact that cytoskeleton is not only required for cell shape and movement but it is crucial also for cell cycle progression and proliferation.…”
Section: Stat Signaling and Cytoskeleton Regulation In Ptclsmentioning
confidence: 90%